Kaempferol suppresses cell migration through the activation of the ERK signaling pathways in ARPE‐19 cells - Chien, Hsiang‐Wen; Wang, Kai; Chang, Yuan‐Yen; Hsieh, Yi‐Hsien; Yu, Nuo‐Yi; Yang, Shun‐Fa; Lin, Hui‐Wen (Environmental toxicology, 2019)
Kaempferol is a flavonoid with anticancer and anti‐metastasis activity in different cancer‐cell lines. However, the underlying mechanisms by which kaempferol acts on human retinal pigment epithelial (ARPE‐19) cells remain unclear. In this study, we demonstrated that kaempferol inhibited migration and invasion in ARPE‐19 cells at non‐toxic dosages. We discovered that kaempferol obviously reduced the enzyme activity and protein expression of matrix metalloproteinase‐2 by increasing the phosphorylated levels of extracellular signal‐regulated kinases 1/2 (ERK1/2) signaling pathways. Additionally, ERK1/2‐specific inhibitor PD98059 significantly reversed kaempferol's inhibitory effects on migration and expression of MMP‐2 in ARPE‐19 cells. Overall, our results are the first to demonstrate that kaempferol is capable of inhibiting cell migration by targeting ERK1/2 signaling in human retinal pigment epithelial cells.